Novel mutation in HPRT1 causing a splicing error with multiple variations. (2nd January 2017) - Baba, Shimpei; Saito, Takashi; Yamada, Yasukazu; Takeshita, Eri; Nomura, Noriko; Yamada, Kenichiro; Wakamatsu, Nobuaki; Sasaki, Masayuki
ABSTRACT: Lesch-Nyhan disease (LND) is a rare X-linked recessive disorder caused by deficiency of the purine salvage enzyme hypoxanthine–guanine phosphoribosyltransferase (HPRT), encoded by the HPRT1. To date, nearly all types of mutations have been reported in the whole gene; however, duplication mutations are rare. We here report the case of a 9-month-old boy with LND. He showed developmental delay, athetosis, and dystonic posture from early infancy, but no self-injurious behaviors. Hyperuricemia was detected, and his HPRT enzyme activity in erythrocytes was completely deficient. A novel duplication mutation (c.372dupT, c.372_374 TTT > c.372_375 TTTT) was identified in exon 4 of the HPRT1, which causes aberrant splicing. This is the third case of a duplication mutation in the HPRT1 that causes splicing error.